CYBERSECURITY DAN PERLINDUNGAN DATA DALAM SISTEM PERPAJAKAN DIGITAL - Megasari Sijabat, Fittry; Widjaja, Gunawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Advances in digital technology have driven the transformation of the taxation system to be more efficient and timely, but they have also created new challenges in terms of cybersecurity and data protection. Digital taxation systems manage large amounts of sensitive data, including taxpayers' personal and financial information, which is a potential target for cyberattacks. This study discusses important measures that need to be implemented to ensure the security and integrity of data in digital taxation systems. These measures include the implementation of encryption technology, strict access control, routine security audits, and security awareness training for staff. A holistic approach and collaboration with technology experts are the main keys to maintaining a secure and reliable taxation system, while maximising the benefits of digitalisation. With these steps, the risk of cyber threats can be minimised, so that the integrity and public trust in the digital taxation system is maintained.